2021
DOI: 10.1007/s11517-021-02482-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle shortening on single-fiber, motor unit, and compound muscle action potentials

Abstract: Even under isometric conditions, muscle contractions are associated with some degree of fiber shortening. The effects of muscle shortening on extracellular electromyographic potentials have not been characterized in detail. Moreover, the anatomical, biophysical, and detection factors influencing the muscle-shortening effects have been neither identified nor understood completely. Herein, we investigated the effects of muscle shortening on the amplitude and duration characteristics of single-fiber, motor unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
2
6
0
1
Order By: Relevance
“…This model revealed two main effects: (1) as the muscle shortens and bulges, the fibers increase their distance from the detection electrode, which results in a decrease of the amplitude of the propagating component; (2) as the muscle shortens, the tendon endings approach the electrodes, thus causing an enlargement of the non-propagating component. Our group proposes a second analytical model, which confirmed the findings of Mesin and colleagues (Rodriguez-Falces and Place 2014 ; Rodriguez-Falces et al 2022 ). In addition to the adjustments in amplitude, our model showed that muscle shortening also provokes a decrease in the duration of the M wave (Rodriguez-Falces et al 2022 ).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…This model revealed two main effects: (1) as the muscle shortens and bulges, the fibers increase their distance from the detection electrode, which results in a decrease of the amplitude of the propagating component; (2) as the muscle shortens, the tendon endings approach the electrodes, thus causing an enlargement of the non-propagating component. Our group proposes a second analytical model, which confirmed the findings of Mesin and colleagues (Rodriguez-Falces and Place 2014 ; Rodriguez-Falces et al 2022 ). In addition to the adjustments in amplitude, our model showed that muscle shortening also provokes a decrease in the duration of the M wave (Rodriguez-Falces et al 2022 ).…”
Section: Introductionsupporting
confidence: 86%
“…Our group proposes a second analytical model, which confirmed the findings of Mesin and colleagues (Rodriguez-Falces and Place 2014 ; Rodriguez-Falces et al 2022 ). In addition to the adjustments in amplitude, our model showed that muscle shortening also provokes a decrease in the duration of the M wave (Rodriguez-Falces et al 2022 ). In the present study, the above simulation results were verified using real M waves evoked at different muscle lengths.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In view of the present findings the assumption that 'the first phase of the belly-tendon M wave results from the propagation of the action potentials along muscle fibres, whereas the second reflects the extinction of these action potentials at the tendon' proposed by Rodriguez-Falces et al (2022) should be revisited. Indeed, here we showed that the belly potential of the vastus lateralis (and tibialis anterior) exhibited a distinct shoulder (or peak) in the first phase, which had a non-propagating character.…”
Section: Practical Implications and Recommendationsmentioning
confidence: 82%
“…Existe uma interação entre os sistemas que compõe a mandíbula e a região cervical devido às comunicações neurológicas e biomecânicas existentes (PACKER et al, 2014). Os potenciais de ação das fibras musculares promovem o deslizamento de filamentos de actina e miosina, que produz padrões funcionais como a contração muscular isométrica e/ou isotônica que é interceptado pela eletromiografia de superfície, sendo um importante método de estudo clínico que produz resultados com a função de demonstrar alterações que o organismo humano pode estar sofrendo decorrentes das patologias degenerativas sistêmicas (MATSUI et al, 2017;MOUSA;PATIL;LYNCH, 2017;RODRIGUEZ-FALCES;MALANDA;NAVALLAS, 2021).…”
Section: Lista De Tabelasunclassified